ANALISIS KEMENANGAN MARZUQI-ANDI PADA PILKADA JEPARA 2017 - Fikrian Akbar Islamsyah; Fitriyah . (Journal of Politic and Government Studies, 2018)
The election of the district head always become an interesting phenomenon to discuss, because it always have a different characteristic on each district. This research aims to determine the victory factors of Marzuqi-Dian in Jepara’s election 2017. This research become interesting because of even there was a huge modalities differences between the two candidates and the corruption case that he faces, Marzuqi still win the election.The method in this research is using analytics descriptive with qualitative methods. The sampling technique of this research is using purpossive sampling. Methods of data collection in this research are using interview, observation, and documents that related to this research.The result showed that there are four factors that affect Marzuqi’s victory factors to win the election, that is 1) Marzuqi’s figure displayed as a Kyai and a humble person that people loves, 2) Andi as a PDI-P politic engine driver, which the only one political party bearer that beats the nine others, 3) The strength of politic engine, Marzuqi-Dian colaborate to win the election using the network that they have, 4) The strength of victory strategy using one strong and solid political party. The four factors above is an advantages that Marzuqi have to beat the other candidate.Keyword: election, figure, politic strategy, politic marketing.